A Tale of Two Curriculums: The Implications of Curriculum Design on Student Burnout. Issue 3 (20th September 2022) - Sivahop, Jacqueline; Broadfoot, Kirsten; Bowser, Jonathan
Abstract : Introduction: The purpose of this study was to determine whether a difference exists in the 3 subconstructs of burnout between 2 cohorts of physician assistant (PA) students in different curricula, and the impact of 4 modifiable curricular factors on student experiences of burnout. Methods: Using a mixed-methods study design, 86 students completed the Maslach Burnout Inventory–General Survey for Students (MBI-GSS) 8 months postmatriculation. Focus group interviews expanded on the quantitative results and effects of the 4 modifiable factors. Results: No significant statistical difference was found in the emotional exhaustion ( p = 0.35), cynicism ( p = 0.29), or professional efficacy ( p = 0.23) scores between the 2 cohorts of PA students. Students did not describe the exact dimensions of burnout; however, qualitative data provided 5 emergent codes based on their experiences. Discussion: Despite curricular modifications to address student burnout in the Colorado Curriculum, a statistical difference in burnout scores was not found between the 2 student cohorts. Qualitative findings suggest that PA education programs should examine external factors and student-lived experiences that contribute to burnout in addition to curricular components.